Cosmological features of primordial magnetic fields (2018)
Recently, it has been found that our Universe holds magnetic fields in almost all scales probed so far. The fields in galaxies and galaxy clusters have strength of a few μGauss and they are correlated up to Kpc scales. Furthermore, new observational evidence suggests the existence of magnetic fields of 10 −16 Gauss in the intergalactic medium with a correlation length of Mpc. However, the origin of these large scale magnetic fields is one of the most puzzling topics in cosmology and astrophysics. It is assumed that the observed magnetic fields result from the amplification of an initial field produced in the early Universe. Indeed, if those primordial fields were generated in early stages of the Universe, they could have left a distinctive signature on the Cosmic Microwave Background anisotropies (CMB). Thus, one of the most appealing ways of detecting those primordial magnetic fields is through temperature and polarization CMB observations. Therefore, the aim of this thesis is to study the effects on the CMB anisotropy due to primordial magnetic fields and to analyze some favorable scenarios of magnetogenesis constrained by those signatures, including limits on the amplitude of the fields from bounds on CMB non-Gaussianity and background models. In fact, we found out that helicity in the fields plays an important role in the analysis PMFs origin, by generating significant features in the cross-correlation polarization pattern and the increasing of the signal in the reduced CMB bispectrum. In the latter case, we reported that non-causal fields (mainly generated during the inflation epoch) are the most favorable models constrained by CMB observations. Moreover, we have studied the presence of an IR cutoff in the spectra and bispectra finding appealing unique features from primordial magnetic fields. Another important result shown in this thesis, is the equivalence between different approaches of cosmological perturbation theory in the magnetized context. In fact, assuming a magnetized Universe and building gauge invariant quantities in both approaches: the 1 + 3−covariant and the gauge invariant; we found out that those invariants represent the same physical meaning. Besides, we define gauge invariant related to the electromagnetic potentials which in future works, could help us to study magnetogenesis models on perturbed scenarios.